Anchoring type flexible fabric with radiation refrigeration function

CN123005698APending Publication Date: 2026-10-30FUJIAN ZHANGPING JUCHUANG TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611256871.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0009]有鉴于此,本发明提供一种具备辐射制冷功能的锚固型柔性织物,以解决或缓解现有技术中存在的技术问题,至少提供一种有益的选择

Benefits of technology

[0029]一、本发明突破了辐射制冷织物必须形成连续膜层的传统思路,采用点状离散锚固结构,在维持较高太阳反射率和大气窗口红外发射率的同时,显著提高透气舒适性,透气率保留率可达85%以上;与简单浸渍方案相比,本发明透气率更优,同时颗粒锚固牢度提升2~3倍,50次水洗后颗粒保留率超90%,,耐弯折、耐摩擦和耐水洗性能显著优于简单浸渍方案,长期使用性能稳定,真正实现了高制冷效率、高透气舒适、高耐久牢度三者兼得,为辐射制冷织物的产业化落地扫清了核心障碍。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123005698A_ABST
    Figure CN123005698A_ABST
Patent Text Reader

Abstract

The application discloses an anchoring type flexible fabric with a radiation refrigeration function and a preparation method thereof, and belongs to the field of functional textiles and passive refrigeration technology. The fabric comprises a fabric base body, discrete point anchoring structures and functional particles. The anchoring structures are only distributed on the contact interface of the particles and the fibers, the fabric is free of an overall continuous film, and complete connected and breathable pores are reserved. The application breaks through the traditional idea that a radiation refrigeration fabric must form a continuous film layer, adopts point discrete anchoring structures, significantly improves the air permeability comfort while maintaining a high solar reflectivity and atmospheric window infrared emissivity, and the air permeability retention rate can reach more than 85%. Compared with a simple dipping scheme, the air permeability of the application is better, the particle anchoring firmness is improved by 2 to 3 times, the particle retention rate is more than 90% after 50 times of washing, the bending resistance, friction resistance and washing resistance are significantly better than those of the simple dipping scheme, the long-term use performance is stable, and the high refrigeration efficiency, high air permeability comfort and high durability firmness are realized, which sweeps away the core obstacle for the industrialization of the radiation refrigeration fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional textile materials and passive radiative cooling technology, specifically to an anchoring flexible fabric with radiative cooling function. Background Technology

[0002] Passive radiative cooling technology can cool an object by radiating heat into outer space through atmospheric windows in the form of infrared radiation under zero-energy conditions. It is a cutting-edge cooling technology that combines energy saving and environmental protection. Imbuing flexible fabrics with radiative cooling capabilities can create cooling clothing and sun-shading fabrics, which have significant application value in high-temperature outdoor environments. However, existing radiative cooling fabric technologies still suffer from unresolved performance contradictions, specifically the following drawbacks:

[0003] Continuously laminated cooling fabrics have extremely poor breathability and moisture permeability, resulting in a loss of wearing comfort.

[0004] The current mainstream solution involves coating the fabric surface with a continuous radiation-cooling polymer coating, uniformly dispersing the cooling particles within the coating resin to form a dense, continuous film. While this solution offers high particle loading and reliable cooling performance, it completely blocks the fabric's original fiber gaps, reducing air permeability by over 70% and moisture permeability to less than 30% of the original fabric. When worn as clothing, this prevents the release of sweat, resulting in a stuffy, sticky feeling that completely fails to meet the comfort requirements for everyday wear. Furthermore, the significant difference in thermal expansion coefficients between the continuous film and the fabric matrix makes the film prone to cracking, peeling, and detachment after bending, washing, and sun exposure, resulting in a lifespan of less than 6 months and severely insufficient durability.

[0005] Simple impregnation and loading of particles results in poor adhesion and rapid degradation of cooling performance.

[0006] To preserve fabric breathability, some solutions employ a simple impregnation process, where cooling particles are mixed into a slurry and directly soaked into the fabric. After drying, the particles physically adhere to the fiber surface. This method retains some porosity, but the bond between the particles and fibers relies solely on van der Waals forces, lacking chemical bonding and anchoring, resulting in extremely weak adhesion. After 10 washes and friction cycles, the particle shedding rate exceeds 50%, solar reflectivity and infrared emissivity decrease significantly, and cooling performance is reduced by more than half. After one month of outdoor use, performance is essentially lost, failing to meet long-term usage requirements and only providing a short-term, one-time effect, lacking any industrial-scale practical value.

[0007] Existing anchoring technologies cannot simultaneously address both "discrete anchoring" and "non-continuous membrane" issues.

[0008] A few existing technologies attempt to construct anchoring structures on the fiber surface to improve particle strength, but all employ high-temperature film-forming processes. The resin ultimately spreads into a continuous film on the fiber surface and between fibers, essentially remaining a coating structure, albeit a thinner one. This still clogs most pores, resulting in limited improvement in breathability and comfort. Furthermore, the single resin system has poor interfacial compatibility with inorganic particles and organic fibers, leading to an anchoring force increase of less than 30%, failing to fundamentally resolve the core contradiction between "anchoring strength" and "breathability porosity." No solution in the industry has yet achieved the triple goals of: particles anchored to fibers in a discrete point pattern, no overall continuous film coating, and strong particle bonding. Therefore, an anchoring flexible fabric with radiative cooling function is proposed. Summary of the Invention

[0009] In view of this, the present invention provides an anchoring flexible fabric with radiative cooling function to solve or alleviate the technical problems existing in the prior art, and at least provides a beneficial alternative.

[0010] The technical solution of this invention is implemented as follows: an anchoring flexible fabric with radiative cooling function, comprising a fabric matrix and functional particles.

[0011] The functional particles are discretely anchored to the surface of a single fiber in the fabric matrix and to the gaps between interwoven fibers through an anchoring structure.

[0012] The anchoring structure consists of cross-linked and cured dot-shaped resin anchoring points, which are distributed only at the contact interface between the functional particles and the fibers. Each anchoring point is independent of the others, and the fabric as a whole does not have a continuous coating that covers all the fibers.

[0013] The fabric matrix has interconnected air-permeable pores and inter-fiber pores between fibers and between functional particles.

[0014] More preferably, the diameter of a single anchoring structure 2 is 1~10μm.

[0015] More preferably, the fabric matrix is ​​a woven, knitted, or nonwoven fabric, made of polyester fiber, polyamide fiber, cotton fiber, linen fiber, or a blend of these fibers, with a weight of 50~300g / ㎡.

[0016] More preferably, the functional particles 3 are compound inorganic particles, comprising 40%~70% high reflectance components and 30%~60% high emissivity components by mass; the high reflectance components are one or more of rutile titanium dioxide, barium sulfate, and zinc oxide, with a particle size of 0.3~2μm; the high emissivity components are one or more of silica aerogel, boron nitride, and silicon carbide, with a particle size of 1~5μm; the loading of the functional particles is 5%~25% of the total mass of the fabric.

[0017] More preferably, the anchoring structure is formed by curing a cross-linked resin system; the cross-linked resin system comprises, by mass parts: 30-60 parts of modified silane epoxy resin, 20-50 parts of waterborne polyurethane, 2-8 parts of silane coupling agent, 1-5 parts of waterborne amine curing agent, and 0.5-2 parts of additives.

[0018] Further preferred, the finished fabric retains ≥85% of the air permeability of the original fabric; after 50 washes, the retention rate of functional particles in the fabric is ≥90%.

[0019] A method for preparing an anchoring flexible fabric with radiative cooling function includes the following steps:

[0020] S1 pretreats the fabric matrix and introduces active groups on the fiber surface;

[0021] S2 disperses functional particles, crosslinking resin, coupling agent, and curing agent in deionized water to prepare an anchoring functional liquid.

[0022] S3 immerses the fabric in the anchoring liquid and controls the liquid rate to 40%~80% by rolling, so that the functional liquid is dispersed and adhered to the fiber surface without forming a continuous liquid film.

[0023] S4 undergoes a two-stage drying and curing process: first, it is pre-dried at 60~80℃ for 3~5 minutes, and then cross-linked and cured at 90~110℃ for 5~10 minutes, so that the resin forms a discrete anchoring structure at the contact point between the particles and the fibers.

[0024] After finishing and shaping with S5, the finished product is obtained.

[0025] More preferably, the solid content of the anchoring fluid in step S2 is 10% to 30%.

[0026] In a further preferred embodiment, in step S2, the functional particles are first surface-modified with a silane coupling agent, and then crosslinking resin and curing agent are added.

[0027] An anchoring flexible fabric with radiative cooling function is used as an outdoor sun protection clothing, building sunshade film material, vehicle sunshade fabric, outdoor tent or cold chain insulation covering material.

[0028] The embodiments of the present invention have the following advantages due to the adoption of the above technical solutions:

[0029] I. This invention breaks through the traditional approach that radiation-cooling fabrics must form a continuous film layer. It adopts a point-like discrete anchoring structure, which significantly improves breathability and comfort while maintaining high solar reflectivity and atmospheric window infrared emissivity. The breathability retention rate can reach over 85%. Compared with simple impregnation, this invention has better breathability and increases particle anchoring strength by 2 to 3 times. After 50 washes, the particle retention rate exceeds 90%. The bending resistance, abrasion resistance, and washing resistance are significantly better than simple impregnation. The long-term performance is stable, truly achieving a balance of high cooling efficiency, high breathability and comfort, and high durability. This removes the core obstacles to the industrialization of radiation-cooling fabrics.

[0030] II. This invention employs a crosslinking system of modified silane epoxy resin and waterborne polyurethane, combined with silane coupling agent for interface modification: the epoxy resin side is tightly bonded to inorganic particles, while the polyurethane side is firmly attached to organic fibers. The coupling agent builds chemical bridges at the two-phase interface, forming a stable three-phase interface of "fiber-resin-particle". Testing shows that the particle peel strength is 8-10 times that of physical adhesion and 3-4 times that of single resin anchoring. Washability, abrasion resistance, and bending resistance are all significantly improved, extending the fabric's service life by more than 3 times, greatly enhancing the product's life-cycle value.

[0031] Third, the highest temperature in the entire preparation process of this invention does not exceed 110℃, which is a low-temperature processing technology. It will not damage the mechanical properties and soft hand feel of the fabric matrix. It can be adapted to almost all common flexible fabrics such as polyester, nylon, cotton, linen, and blends, and has a very wide range of applications. The process can be achieved based on the conventional impregnation, rolling, drying, and setting equipment in the textile industry. No special equipment needs to be added. Only the process parameters need to be optimized to complete the production line transformation. The transformation cost is low, and it can be continuously mass-produced. The processing cost per meter is only 60% of that of the coating solution, which has a strong advantage in industrialization.

[0032] The above overview is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments, and features described above, further aspects, embodiments, and features of the invention will become readily apparent from the accompanying drawings and the following detailed description. Attached Figure Description

[0033] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0034] Figure 1 This is a three-dimensional structural diagram of the present invention;

[0035] Figure 2 This is a side view cross-sectional structural diagram of the present invention;

[0036] Figure 3 This is a top view of the structure of the present invention.

[0037] Reference numerals: 1. Fabric matrix; 2. Anchoring structure; 3. Functional particles; 4. Breathable pores; 5. Interfiber pores. Detailed Implementation

[0038] In the following description, only certain exemplary embodiments are briefly described. As those skilled in the art will recognize, the described embodiments can be modified in various ways without departing from the spirit or scope of the invention. Therefore, the drawings and description are considered to be exemplary in nature and not restrictive.

[0039] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings.

[0040] like Figure 1-3 As shown, this embodiment of the invention provides an anchoring flexible fabric with radiative cooling function, comprising a fabric matrix 1 and functional particles 3.

[0041] Functional particles 3 are discretely anchored to the surface of a single fiber and the gaps between interwoven fibers in the fabric matrix 1 through the anchoring structure 2.

[0042] Anchoring structure 2 consists of cross-linked and cured dot-shaped resin anchoring points, which are only distributed at the interface between functional particles 3 and fibers. Each anchoring point is independent of the others, and the fabric as a whole does not have a continuous coating that covers all fibers.

[0043] The fabric matrix 1 has interconnected air pores 4 and inter-fiber pores 5 between the fibers and between the functional particles 3.

[0044] In one embodiment, the diameter of a single anchoring structure 2 is 1~10μm.

[0045] In one embodiment, the fabric substrate 1 is a woven, knitted, or nonwoven fabric, made of polyester fiber, polyamide fiber, cotton fiber, linen fiber, or blended fiber thereof, with a weight of 50~300g / ㎡.

[0046] In one embodiment, the functional particle 3 is a compound inorganic particle, comprising 40% to 70% high reflectance component and 30% to 60% high emissivity component by mass; the high reflectance component is one or more of rutile titanium dioxide, barium sulfate, and zinc oxide, with a particle size of 0.3 to 2 μm; the high emissivity component is one or more of silica aerogel, boron nitride, and silicon carbide, with a particle size of 1 to 5 μm; the loading of the functional particle is 5% to 25% of the total mass of the fabric.

[0047] In one embodiment, the anchoring structure 2 is formed by curing a cross-linked resin system; the cross-linked resin system comprises, by mass parts: 30-60 parts of modified silane epoxy resin, 20-50 parts of waterborne polyurethane, 2-8 parts of silane coupling agent, 1-5 parts of waterborne amine curing agent, and 0.5-2 parts of additives.

[0048] In one embodiment, the finished fabric retains ≥85% of the air permeability relative to the virgin fabric; after 50 washes, the retention rate of functional particles within the fabric is ≥90%.

[0049] A method for preparing an anchoring flexible fabric with radiative cooling function includes the following steps:

[0050] S1 pretreats the fabric matrix and introduces active groups on the fiber surface;

[0051] S2 disperses functional particles, crosslinking resin, coupling agent, and curing agent in deionized water to prepare an anchoring functional liquid.

[0052] S3 immerses the fabric in the anchoring liquid and controls the liquid rate to 40%~80% by rolling, so that the functional liquid is dispersed and adhered to the fiber surface without forming a continuous liquid film.

[0053] S4 undergoes a two-stage drying and curing process: first, it is pre-dried at 60~80℃ for 3~5 minutes, and then cross-linked and cured at 90~110℃ for 5~10 minutes, so that the resin forms a discrete anchoring structure at the contact point between the particles and the fibers.

[0054] After finishing and shaping with S5, the finished product is obtained.

[0055] In one embodiment, the solid content of the anchoring fluid in step S2 is 10% to 30%.

[0056] In one embodiment, in step S2, the functional particles are first surface-modified with a silane coupling agent, and then crosslinking resin and curing agent are added.

[0057] An anchoring flexible fabric with radiative cooling function is used as an outdoor sun protection clothing, building sunshade film material, vehicle sunshade fabric, outdoor tent or cold chain insulation covering material.

[0058] Example 1

[0059] This embodiment provides a polyester-based anchoring type cooling fabric.

[0060] Raw material preparation:

[0061] Fabric matrix: Polyester woven fabric, weight 150g / m²;

[0062] Functional particles: a compound of rutile titanium dioxide (55 parts, average particle size 0.5 μm) and silica aerogel (45 parts, average particle size 3 μm), with a loading of 15% of the total fabric mass;

[0063] Crosslinking resin: 45 parts modified silane epoxy resin, 35 parts waterborne polyurethane, 5 parts KH550 coupling agent, 3 parts waterborne amine curing agent, and 2 parts dispersant.

[0064] Preparation process:

[0065] S1 Pretreatment: The polyester fabric is immersed in NaOH solution for alkali reduction treatment, hydroxyl active groups are introduced on the fiber surface, and then washed and dried.

[0066] S2 anchoring functional liquid preparation: Add functional particles to deionized water, first add KH550 coupling agent for surface modification, stir and disperse; then add modified silane epoxy resin, waterborne polyurethane, curing agent and dispersant, disperse at high speed until uniform, and prepare an anchoring functional liquid with a solid content of 20%.

[0067] S3 Discrete Impregnation Anchoring: The pretreated fabric is immersed in the anchoring functional liquid, and after being taken out, it is quantitatively rolled by a rolling mill to control the liquid content to 60%, so that the functional liquid adheres to the fiber surface in the form of discrete droplets and does not form a continuous liquid film.

[0068] S4 Low-Temperature Crosslinking and Curing: The impregnated fabric is sent into an oven and pre-dried at 70°C for 4 minutes, and then crosslinked and cured at 100°C for 8 minutes, so that the resin is cured at the contact point between the particles and the fibers to form a discrete anchoring structure.

[0069] S5 finishing and setting: The cured fabric is then stretched and set to obtain the finished product.

[0070] Finished product structure characterization: Scanning electron microscopy revealed that the functional particles were discretely anchored to the fiber surface without continuous coating. The anchoring points were independently distributed in a dotted pattern, and the pores between the fibers were intact. Performance test results are shown in Table 1.

[0071] Example 2

[0072] This embodiment provides a nylon-based anchoring cooling fabric.

[0073] Raw material preparation:

[0074] Fabric matrix: Nylon knitted fabric, weight 100g / ㎡;

[0075] Functional particles: a compound of barium sulfate (65 parts, average particle size 1 μm) and boron nitride (35 parts, average particle size 2 μm), with a loading of 20% of the total fabric mass;

[0076] Crosslinking resin: 55 parts modified silane epoxy resin, 25 parts waterborne polyurethane, 6 parts KH570 coupling agent, 4 parts waterborne amine curing agent, and 1.5 parts dispersant.

[0077] Preparation process: basically the same as in Example 1, except that: S1 pretreatment uses plasma treatment to introduce active groups; the anchoring function liquid-solid content in S2 is 25%; the liquid carrying rate in S3 is controlled at 70%; and the pre-baking conditions in S4 are 80℃ for 3 min and cross-linking curing conditions are 105℃ for 7 min.

[0078] The performance test results of the finished product are shown in Table 1.

[0079] Example 3

[0080] This embodiment provides a cotton-linen blended anchoring type cooling fabric.

[0081] Raw material preparation:

[0082] Fabric matrix: Cotton / linen blend woven fabric, weight 200g / ㎡;

[0083] Functional particles: a compound of zinc oxide (40 parts, average particle size 0.8 μm) and silicon carbide (60 parts, average particle size 4 μm), with a loading of 10% of the total fabric mass;

[0084] Crosslinking resin: 35 parts modified silane epoxy resin, 45 parts waterborne polyurethane, 4 parts KH550 coupling agent, 2 parts waterborne amine curing agent, and 1 part dispersant.

[0085] Preparation process: basically the same as in Example 1, except that: S1 pretreatment adopts conventional desizing and refining process; the anchoring function liquid-solid content in S2 is 15%; the liquid carrying rate in S3 is controlled at 50%; the pre-drying conditions in S4 are 65℃ for 5 min and cross-linking curing conditions are 95℃ for 10 min.

[0086] The performance test results of the finished product are shown in Table 1.

[0087] Comparative Example 1: Continuously Coated Cooling Fabric (Prior Art)

[0088] The same batch of polyester woven fabric is coated with a continuous radiation cooling coating (with the same functional particles and pure polyurethane resin), with a coating thickness of 20μm, to form a complete continuous film.

[0089] Comparative Example 2: Simple Impregnation Type Cooling Fabric (Prior Art)

[0090] Using polyester woven fabric from the same batch, the particles with the same function are simply impregnated with an aqueous solution, anchored without cross-linking resin, and directly dried, so that the particles physically adhere to the fiber surface.

[0091] Performance test comparison

[0092] Core performance tests were conducted on three sets of example cases and two sets of comparative cases. The results are shown in the table below:

[0093] Solar reflectivity (0.3~2.5μm) 93.2% 94.5% 91.6% 92.8% 86.3% Atmospheric window infrared emissivity 94.1% 93.7% 92.9% 93.5% 90.2% Air permeability retention rate (relative to the original fabric) 91% 87% 93% 22% 78% Particle retention rate after 50 washes 94.3% 92.7% 95.1% 71.5% (film cracking) 32.8% Appearance after 1000 bends No abnormalities No abnormalities No abnormalities Film cracking and peeling Large amounts of particles fell off Temperature drop at noon 5.8℃ 6.3℃ 5.2℃ 5.6℃ 3.1℃

[0094] The test results show that the cooling performance of this invention is comparable to that of the continuous coating scheme and far superior to the simple impregnation scheme; the air permeability retention rate is much higher than that of the continuous coating scheme and close to that of the original fabric; the water resistance and bending resistance are significantly better than the two existing technologies, completely resolving the performance triangle contradiction and demonstrating outstanding technical effects.

[0095] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various variations or substitutions within the technical scope disclosed in the present invention, and these should all be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. An anchoring flexible fabric with radiative cooling function, comprising a fabric matrix (1) and functional particles (3), characterized in that, The functional particles (3) are discretely anchored to the surface of a single fiber of the fabric matrix (1) and at the gaps between interwoven fibers through the anchoring structure (2); The anchoring structure (2) is a cross-linked and cured dot-shaped resin anchoring point, which is only distributed at the contact interface between the functional particles (3) and the fiber. Each anchoring point is independent of the others, and the fabric as a whole does not have a continuous coating covering all the fibers. The fabric matrix (1) has interconnected air-permeable pores (4) and inter-fiber pores (5) between fibers and between functional particles (3).

2. The anchoring flexible fabric with radiative cooling function according to claim 1, characterized in that, The diameter of a single anchoring structure (2) is 1~10μm.

3. The anchoring flexible fabric with radiative cooling function according to claim 1, characterized in that, The fabric matrix (1) is a woven, knitted or nonwoven fabric, made of polyester fiber, polyamide fiber, cotton fiber, hemp fiber or blended fiber, with a weight of 50~300g / ㎡.

4. The anchoring flexible fabric with radiative cooling function according to claim 1, characterized in that, The functional particles (3) are compound inorganic particles, comprising 40% to 70% high reflectivity components and 30% to 60% high emissivity components by mass; the high reflectivity components are one or more of rutile titanium dioxide, barium sulfate, and zinc oxide, with a particle size of 0.3 to 2 μm; the high emissivity components are one or more of silica aerogel, boron nitride, and silicon carbide, with a particle size of 1 to 5 μm; the loading of the functional particles is 5% to 25% of the total mass of the fabric.

5. The anchoring flexible fabric with radiative cooling function according to claim 1, characterized in that, The anchoring structure (2) is formed by curing a cross-linked resin system; the cross-linked resin system includes, by mass parts: 30-60 parts of modified silane epoxy resin, 20-50 parts of waterborne polyurethane, 2-8 parts of silane coupling agent, 1-5 parts of waterborne amine curing agent, and 0.5-2 parts of additives.

6. The anchoring flexible fabric with radiative cooling function according to claim 1, characterized in that, The finished fabric retains ≥85% of the air permeability of the original fabric; after 50 washes, the retention rate of functional particles in the fabric is ≥90%.

7. A method for preparing an anchoring flexible fabric with radiative cooling function, characterized in that, Includes the following steps: S1 pretreats the fabric matrix and introduces active groups on the fiber surface; S2 disperses functional particles, crosslinking resin, coupling agent, and curing agent in deionized water to prepare an anchoring functional liquid. S3 immerses the fabric in the anchoring liquid and controls the liquid rate to 40%~80% by rolling, so that the functional liquid is dispersed and adhered to the fiber surface without forming a continuous liquid film. S4 undergoes a two-stage drying and curing process: first, it is pre-dried at 60~80℃ for 3~5 minutes, and then cross-linked and cured at 90~110℃ for 5~10 minutes, so that the resin forms a discrete anchoring structure at the contact point between the particles and the fibers. After finishing and shaping with S5, the finished product is obtained.

8. The preparation method according to claim 7, characterized in that, The solid content of the anchoring fluid in step S2 is 10%~30%.

9. The preparation method according to claim 7, characterized in that, In step S2, the functional particles are first surface modified with a silane coupling agent, and then crosslinking resin and curing agent are added.

10. The application of the anchoring flexible fabric with radiation cooling function as described in any one of claims 1 to 6 as outdoor sun protection clothing, building sunshade film material, vehicle sunshade fabric, outdoor tent or cold chain insulation covering material.